A brief screening instrument for the early identification of autism spectrum disorders in Serbia: A psychometric study of the Minute for autism (MAUT) instrument - Stevanović, Dejan; Kovačić, Zoran; Cvijetić Vukčević, Marija; Milević, Aleksa; Cvetković Brkić, Slavica; Dodić, Andrijana; Mrvić, Jelena (Medicinski časopis, 2025)
Objective: This study evaluates the psychometric properties of a brief screening tool for autism spectrum disorder (ASD) within a cohort of children with neurodevelopmental disabilities and typically developing children.Methods: The study involved 306 children (208 boys, representing 68%; mean age 44.6 ± 13.6 months), with data collected from both parents and evaluators (including child psychiatrists, special education teachers, speech therapists, pedagogues, and preschool teachers). The prototype instrument, Minute for Autism (MAUT), consisting of 15 items assessing key ASD symptoms, was tested.Results: Analysis identified a single factor represented by 7 items in parental assessments (accounting for 53.3% of variance) and 10 items in evaluator assessments (accounting for 53.6% of variance), with primary indicators focusing on measures of social engagement. Four dominant items emerged: "the child looks at you when you speak or play with them," "the child addresses others," "the child talks," and "the child brings objects/toys to show you." These items demonstrated a sensitivity of 72.9% for parental assessments and 84.8% for evaluator assessments. The specificity for detecting ASD, as opposed to typical development, was high (94.1% for parents and 100% for evaluators), although it was lower for differentiating ASD from complex neurodevelopmental disorders (70.8% for parents and 46.2% for evaluators).Conclusion: The findings suggest that an instrument featuring only four items related to social engagement could be sufficiently effective for rapid and early ASD screening. Evaluators appeared more sensitive to ASD identification than parents, whereas parents were more accurate in distinguishing ASD from other disorders. The primary challenge remains in differentiating ASD from other neurodevelopmental disorders, where the instrument may produce false positives. Future studies should assess the instrument's efficacy in populations of at-risk children.